What factors affect physicians' labour supply: Comparing structural discrete choice and reduced‐form approaches. (4th October 2017) - Kalb, Guyonne; Kuehnle, Daniel; Scott, Anthony; Cheng, Terence Chai; Jeon, Sung‐Hee
Summary: Little is known about the response of physicians to changes in compensation: Do increases in compensation increase or decrease labour supply? In this paper, we estimate wage elasticities for physicians. We apply both a structural discrete choice approach and a reduced‐form approach to examine how these different approaches affect wage elasticities at the intensive margin. Using uniquely rich data collected from a large sample of general practitioners (GPs) and specialists in Australia, we estimate 3 alternative utility specifications (quadratic, translog, and box‐cox utility functions) in the structural approach, as well as a reduced‐form specification, separately for men and women. Australian data is particularly suited for this analysis due to a lack of regulation of physicians' fees leading to variation in earnings. All models predict small negative wage elasticities for male and female GPs and specialists passing several sensitivity checks. For this high‐income and long‐working‐hours population, the translog and box‐cox utility functions outperform the quadratic utility function. Simulating the effects of 5% and 10% wage increases at the intensive margin slightly reduces the full‐time equivalent supply of male GPs, and to a lesser extent of male specialists and female GPs.